IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL DALAM MENCIPTAKAN LULUSAN SIAP KERJA DI SMK NEGERI 10 LUWU - Elpy; Alimuddin; Firmansyah (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This study aims to describe the implementation of the Internal Quality Assurance System (SPMI) in producing work-ready graduates at SMK Negeri 10 Luwu and identify the obstacles encountered in its implementation. This study used a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation studies. The research subjects included the principal, teachers, and students. The results indicate that the implementation of SPMI at SMK Negeri 10 Luwu has been systematically implemented through the PPEPP cycle (Mapping, Implementation, Evaluation, Control, and Standard Setting). Quality mapping is conducted periodically to identify achievements and needs for quality improvement. Program implementation is carried out through improving the quality of learning and collaborating with industry. Evaluations are conducted routinely to assess standard achievement, followed by control measures for improvement, and the establishment of new standards as a form of continuous quality improvement. This implementation contributes to graduates' work-readiness, characterized by competency in expertise, technical skills, practical abilities, and soft skills. However, obstacles encountered include limited infrastructure and uneven absorption of graduates into the workforce.